Hysterectomy and incidence of depressive symptoms in midlife women: the Australian Longitudinal Study on Women's Health. (13th February 2017) - Wilson, L.; Pandeya, N.; Byles, J.; Mishra, G.
Abstract : Aims: There is limited longitudinal research that has looked at the longer term incidence of depressive symptoms, comparing women with a hysterectomy to women without a hysterectomy. We aimed to investigate the association between hysterectomy status and the 12-year incidence of depressive symptoms in a mid-aged cohort of Australian women, and whether these relationships were modified by use of exogenous hormones. Methods: We used generalised estimating equation models for binary outcome data to assess the associations of the incidence of depressive symptoms (measured by the 10-item Centre for Epidemiologic Studies Depression Scale) across five surveys over a 12-year period, in women with a hysterectomy with ovarian conservation, or a hysterectomy with bilateral oophorectomy compared with women without a hysterectomy. We further stratified women with hysterectomy by their current use of menopausal hormone therapy (MHT). Women who reported prior treatment for depression were excluded from the analysis. Results: Compared with women without a hysterectomy ( n = 4002), both women with a hysterectomy with ovarian conservation ( n = 884) and women with a hysterectomy and bilateral oophorectomy ( n = 450) had a higher risk of depressive symptoms (relative risk (RR) 1.20; 95% confidence interval (CI) 1.06–1.36 and RR 1.44; 95% CI 1.22–1.68, respectively). There were differences in the strength of the risk for women with a hysterectomy with ovarian conservation, compared with those without, when we stratified by current MHT use. Compared with women without a hysterectomy who did not use MHT, women with a hysterectomy with ovarian conservation who were also MHT users had a higher risk of depressive symptoms (RR 1.57; 95% CI 1.31–1.88) than women with a hysterectomy with ovarian conservation but did not use MHT (RR 1.17; 95% CI 1.02–1.35). For women with a hysterectomy and bilateral oophorectomy, MHT use did not attenuate the risk. We could not rule out, however, that the higher risk seen among MHT users may be due to confounding by indication, i.e. MHT was prescribed to treat depressive symptoms, but their depressive symptoms persisted. Conclusions: Women with a hysterectomy (with and without bilateral oophorectomy) have a higher risk of new incidence of depressive symptoms in the longer term that was not explained by lifestyle or socio-economic factors.